2016
DOI: 10.1155/2016/7472340
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Miswak as Toothbrush for Orthodontic Patient

Abstract: This case report presents a patient who is undergoing orthodontic treatment with upper and lower fixed appliance. An interesting point on this case is that the patient only uses Miswak as her oral hygiene tool due to her religious belief. The oral hygiene protocol was allowed and her oral health was closely monitored throughout her orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to Azaripour, based on a 3-week analysis using toothpaste containing extracts of Siwak (S. persica), showed that it significantly reduces gingival inflammation and recommends it as an alternative herbal toothpaste used by the public [24,30]. However, in this study, a respondent was unable to experience a decrease in plaque score; this may be caused by lack of brushing duration or improper techniques.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…According to Azaripour, based on a 3-week analysis using toothpaste containing extracts of Siwak (S. persica), showed that it significantly reduces gingival inflammation and recommends it as an alternative herbal toothpaste used by the public [24,30]. However, in this study, a respondent was unable to experience a decrease in plaque score; this may be caused by lack of brushing duration or improper techniques.…”
Section: Discussionmentioning
confidence: 81%
“…The reduction of plaque occurring in groups using Siwak toothpaste might be supported by the potential of S. persica in eliminating its mechanical and biological properties such as antibacterial, antifungal, and antiplaque [23]. S. persica has many beneficial ingredients such as fluoride which plays a role as anticariogenic; silica acts as an abrasive; potassium sulfate and calcium sulfate inhibit demineralization and induce remineralization; tannins, saponins, and Vitamin C help to heal and repair tissues; and chlorides inhibit the formation of calculus [19,24]. The ingredient is able to reduce the amount of plaque accumulation in the teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation